Returns to office in national and local politics - Kaisa Kotakorpi; Panu Poutvaara; Marko Tervio (Aboa Centre for Economics (ACE), 2013)
We study the returns to political office using data from Finnish parliamentary elections in 1970-2007 and municipal elections in 1996-2008. The discontinuity of electoral outcomes in individual candidate votes allows us to estimate the causal effect of being electedon subsequent income. Getting elected to parliament increases annual earnings initially by about 20 000 euro, but most of this effect fades out over time. Getting elected to a municipal council has a positive effect of about 1000 euro on subsequent annual earnings.
Keywords: D72; 330; returns to office; elections; regression discontinuity